Análisis de la relación de los homicidios y el desempleo en Ecuador, durante el periodo 1990-2020 - Lucas Jadan, Dejhanyra Stefania (2023)
Homicides have economic effects due to the high costs of controlling the level of insecurity. In 2020, Ecuador registered a homicide rate of 7.78% compared to the 17.2% in Latin America, being the one in this region that contributes with a third of homicides worldwide. The objective of this research was to evaluate the relationship between homicides and unemployment in Ecuador, during the period 1990-2020, through statistical and econometric techniques, to propose solutions so that decision makers can consider them, and in this way, allows them to reduce homicides and improve people's well-being. Three cointegration econometric techniques for time series were used: a Vector Autoregressive (VAR) model, an Error Correction (VEC) model, and Granger causality. The results showed that homicides in Ecuador are not related to short- and long-term unemployment, but rather, long-term homicides result from high corruption and immigrant influx. In the short term, human capital positively affects homicides due to its low quality in its development. Regarding the causal link of the variables. Bidirectional causality was found between human capital and homicides, and unidirectional causality from immigration to homicides. The policy implications aim to eradicate corruption, control the entry of immigrants, and improve human capital to counteract the increase in homicides and prevent crime from limiting the country's development.